2022
DOI: 10.1155/2022/7553928
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of miR-214 Alleviates Renal Interstitial Fibrosis by Targeting the Regulation of the PTEN/PI3K/AKT Signalling Pathway

Abstract: The microRNA-214 (miR-214) precursor is formed by the DNM3 gene on human chromosome 1q24.3, which is encoded and transcribed in the nucleus and processed into mature miR-214 in the cytoplasm. Association of miR-214 with the interstitial fibrosis of the kidney has been reported in existing research. Renal interstitial fibrosis is considered necessary during the process of various renal injuries in chronic kidney disease (CKD). One of the important mechanisms is the TGF- (transforming growth factor-) β1-stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In response to acute or chronic kidney injury, the MAPK pathway was obviously activated as evidenced by the increased phosphorylation of P38, ERK1/2, and JNK, which exerts proinflammatory, proapoptotic, and profibrotic impacts during renal I/R injury and renal fibrosis. , Inhibiting the activation of the MAPK pathway was authenticated to significantly ameliorate AKI and renal fibrosis. ,, The enriched top 5 pathways of those 40 intersected genes in order are pathways in cancer, MAPK, PI3K-Akt, human cytomegalovirus infection, and chemical carcinogenesis-receptor activation pathways during KEGG enrichment analysis. The PI3K-Akt signaling pathway is not as consistent as the MAPK pathway in its role in renal I/R injury and renal fibrosis, whereas activating the PI3K-Akt pathway induced the process of TGF-β1-induced EMT and relieved renal I/R injury. , Previous studies revealed that CAD attenuated renal cyst enlargement, LPS-induced lung sepsis, and carrageenan-induced paw edema by inhibiting the MAPK signaling pathway. ,, The bioinformatic analyses and established studies seem to suggest that the MAPK signaling pathway participated in the regulation of renal I/R and UUO injuries during CAD administration. In our animal and cell models, CAD employment markedly mitigated the activation of MAPK NF-κB cascade to reduce renal I/R and UUO damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In response to acute or chronic kidney injury, the MAPK pathway was obviously activated as evidenced by the increased phosphorylation of P38, ERK1/2, and JNK, which exerts proinflammatory, proapoptotic, and profibrotic impacts during renal I/R injury and renal fibrosis. , Inhibiting the activation of the MAPK pathway was authenticated to significantly ameliorate AKI and renal fibrosis. ,, The enriched top 5 pathways of those 40 intersected genes in order are pathways in cancer, MAPK, PI3K-Akt, human cytomegalovirus infection, and chemical carcinogenesis-receptor activation pathways during KEGG enrichment analysis. The PI3K-Akt signaling pathway is not as consistent as the MAPK pathway in its role in renal I/R injury and renal fibrosis, whereas activating the PI3K-Akt pathway induced the process of TGF-β1-induced EMT and relieved renal I/R injury. , Previous studies revealed that CAD attenuated renal cyst enlargement, LPS-induced lung sepsis, and carrageenan-induced paw edema by inhibiting the MAPK signaling pathway. ,, The bioinformatic analyses and established studies seem to suggest that the MAPK signaling pathway participated in the regulation of renal I/R and UUO injuries during CAD administration. In our animal and cell models, CAD employment markedly mitigated the activation of MAPK NF-κB cascade to reduce renal I/R and UUO damage.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K-Akt signaling pathway is not as consistent as the MAPK pathway in its role in renal I/R injury and renal fibrosis, whereas activating the PI3K-Akt pathway induced the process of TGF-β1-induced EMT and relieved renal I/R injury. 9,23 Previous studies revealed that CAD attenuated renal cyst enlargement, LPS-induced lung sepsis, and carrageenan-induced paw edema by inhibiting the MAPK signaling pathway. 17,29,30 The bioinformatic analyses and established studies seem to suggest that the MAPK signaling pathway participated in the regulation of renal I/R and UUO injuries during CAD administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, TGF‐β1‐induced EMT is mediated by microRNA‐214 (miR‐214) precursor (miR‐214‐3p; Hou et al, 2022). This microRNA downregulates phosphatase and tensin homolog and activates PI3K/AKT signaling pathway (Hou et al, 2022). TGF‐β also induces expression of alternative polyadenylation writer (cleavage stimulation factor 2 or CSTF2) in TECs (Tan et al, 2022).…”
Section: Emt and Kidney Fibrosismentioning
confidence: 99%
“…TGF‐β1 can also activate the target genes via non‐Smad pathway (Batlle & Massague, 2019; Sheng & Zhuang, 2020; Xu et al, 2016). For example, TGF‐β1‐induced EMT is mediated by microRNA‐214 (miR‐214) precursor (miR‐214‐3p; Hou et al, 2022). This microRNA downregulates phosphatase and tensin homolog and activates PI3K/AKT signaling pathway (Hou et al, 2022).…”
Section: Emt and Kidney Fibrosismentioning
confidence: 99%